From Cash to Accounts : Switching How Women Save in Uganda - Buehren, Niklas (World Bank, Washington, DC, 2016)
In Sub Saharan Africa women are often not protecting their savings through formal devices but instead keeping their savings in more vulnerable savings options. After participating in a savings promotion program, women are more likely to save in semi-formal savings options. Participants moved their cash to semi-formal saving options, such as ROSCAs, but did not go as far as moving to regular bank accounts or other formal savings options. The pilot identified subgroups that may be especially receptive for informational savings campaigns. Women who were illiterate or had been robbed or stolen from in the past one and a half years show significant increases in take-up of formal savings options after participating in the program. The savings mobilization program resulted in reallocation rather than accumulation of monetary wealth.